Estratégias corporativas: diversificação com criação de valor estudo de caso de duas empresas farmacêuticas brasileiras - Almeida, André Marinho (2010)
As one can see the pharmaceutic market has been showing a rather competitive and rich profile on account of different questions that involve economics, financial marketing aspects, researches and development not only relate to the population health, but it is gifted by high profits and the dominancy in most multinational enterprises in the Brazilian scenary. This study brings as a proposal to analyse two Brazilian laboratories and their ways in accomplishing the diversification strategy on their business and avaliating the creation of value with pratical strategies in each organization. Some of these questions revealed themselves of little interest by the logic that each analysed laboratory is inserted. The research had as base the use of interviews with directors and managers of both enterprises, besides the given information got from articles and scientific publications. In the analyse of the diversification strategies practices, the analitic categories allowed to take as base the study for a better understanding and comparison with the two companies. The conclusions make us believe that questions such as: powerful market and economy market, financial aspects and types and degress present strong influency in the divertification strategies having values created for these enterprises, however each one has presented similar particularities and other ones quite different making us believe that adopted strategies do not take or go on straight route in a corporative universe. Also, it is proposed in this work for future studies concerned to the pression of the Brazilian Pharmaceutic Enterprises and how the govern intends to act over the public political to a greater development and autonomy in Brazil.